2016
DOI: 10.7196/ajhpe.2016.v8i2.554
|View full text |Cite
|
Sign up to set email alerts
|

The NOMA track module on nutrition, human rights and governance: Part 2. A transnational curriculum using a human rights-based approach to foster key competencies in nutrition professionals

Abstract: Background. In response to the challenge of the global health needs of the 21st century, four academic institutions in Norway, South Africa and Uganda, each offering a Master's degree in nutrition, collaboratively developed the NOrwegian MAsters (NOMA) track module on nutrition, human rights and governance, integrating a human rights-based approach into graduate education in nutrition. Objective. To capture students' perceptions about the NOMA track module, focusing on the development of key competencies. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…15 Post-test only outcomes were used to measure effectiveness in the remaining studies. Marais et al 16 evaluated the effectiveness of a module in increasing knowledge and awareness around the relationship between human rights, governance and nutrition. The module lasted for 18 weeks, after which self-reflection interviews were carried out with students.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Post-test only outcomes were used to measure effectiveness in the remaining studies. Marais et al 16 evaluated the effectiveness of a module in increasing knowledge and awareness around the relationship between human rights, governance and nutrition. The module lasted for 18 weeks, after which self-reflection interviews were carried out with students.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…After removal of 1679 duplicates, six nutrition only studies were eligible for inclusion (Figure 1 ). Of the six included nutrition studies, four were qualitative 15 , 16 , 17 , 18 and two were quantitative. 19 , 20 Mapping these to the AfN areas of core competency highlighted that a different competency area was assessed within each of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…[4,10] The interactive and participative approach followed in the NOMA track module offered this group of nutrition professionals the unique opportunity to learn how they, as health professionals, could use an HRBA to make a contribution to the realisation of the human right to be free from hunger and achieve nutritional health for all. The way the module affected students' professional competence was reported by Marais et al [9] and indicated an enhanced awareness of their roles as nutrition practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Globally, the need for more fully comprehensive courses in human rights has been identified by academics, [4] as short courses and seminars are regarded as inadequate in equipping healthcare professionals to operationalise the HRBA in all spheres of their individual professions. [9] Although these courses should be based on human rights law, procedures and principles, they should be responsive to the context within which they are offered Research and according to various societies' own ideals. [4,10] The interactive and participative approach followed in the NOMA track module offered this group of nutrition professionals the unique opportunity to learn how they, as health professionals, could use an HRBA to make a contribution to the realisation of the human right to be free from hunger and achieve nutritional health for all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation